Science, technology, and potential applications of therapeutic cloning. - Jie Xu (IEEE Engineering in medicine and biology magazine)
In theory, although ethically debatable, females can now propagate without males and still conceive fertilized (not cloned) embryos by using oocytes and sperm derived through these mechanisms. Another alternative to the cloning technology, which attempts to avoid the current debate on ethics and policy, is the artificial haploidization of somatic cells As reproductive gametes or sex cells (sperm and eggs) are haploid (have half the number of chromosomes), but somatic cells are diploid (chromosomes are doubled), effort has been made to create artificial gametes via reducing the diploid somatic cells into haploid gamete-like cells. Theoretically, these "haploid" cells can subsequently be combined in a fashion similar to fertilization and develop into an embryo. Obviously, this approach may potentially create more ethical debate than therapeutic cloning.